Sensory traits, color, and shelf life of low-dose irradiated, raw, ground beef patties - Luchsinger, S.E.; Kropf, Donald H.; Garc a Zepeda, C.M.; Marsden, James L.; Hunt, Melvin C.; Hollingsworth, M.E.; Stroda, Sally L.; Chambers, Edgar, IV; Kastner, Curtis L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Irradiation of raw ground beef patties had minimal effects on flavor and aroma of patties after cooking. Oxidative rancidity increased when patties were irradiated in aerobic but not in vacuum packages. Irradiation of vacuum-packaged ground beef patties produced a more stable color. In both packaging types, irradiation significantly reduced microbial growth during storage.
Keywords: Beef; Irradiation; Ground beef; Sensory; Color